Investigasi Pengaruh Flow terhadap Pembacaan Suhu Air Sensor DS18B20 pada Shower Therapy - Arianto, Eko (Jurnal Teknologi, 2023)
The shifting lifestyle trends towards prolonged periods of sitting have led to an increase in health issues such as stress, depression, and even hypertension. In the pursuit of maintaining health, therapy, particularly shower therapy, has become a popular choice for its perceived ability to provide warmth, relaxation, and alleviate fatigue. However, questions arise regarding whether the water temperature in shower therapy changes as water flows at specific rates and how this might influence the therapy's effectiveness. This research aims to observe whether the water temperature in shower therapy is affected by the flow rate using the DS18B20 temperature sensor. The method involves measuring the water temperature at rest and while it flows at various flow rates. Water flow is controlled using a dimmer on the booster pump, while temperature measurements are taken using the DS18B20 temperature sensor and water flow meter sensor. The test results indicate that water at temperatures of 38-43°C flowing through pipes experiences an average temperature decrease of approximately 1.53°C. However, the temperature decrease does not exhibit a linear relationship with the flow rate. These findings suggest the possibility of other factors, such as the surface area of the conduit (pipes), influencing the temperature reduction in shower therapy. Hence, further research to examine the impact of the surface area of the conduit on the temperature reduction in shower therapy is warranted to obtain a more comprehensive understanding.